Enzyme additions to sorghum-based diets for finishing pigs - J S Park; Robert H Hines; C A Maloney; H Cao; D J Lee; Joe D Hancock; Joel M DeRouchey (Kansas Agricultural Experiment Station Research Reports, 1998)
Three experiments were conducted to determine the effects of a sorghum-specific enzyme supplementation on growth performance of finishing pigs. Although positive trends occurred, the sorghum-specific enzymes used in our experiments did not yield large and(or) consistent improvements in growth performance or nutrient digestibility in finishing pigs.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Sorghum; Enzyme; Finishing pigs